INTERVENSI TERBATAS UNTUK MENGATASI MISKONSEPSI KORELASIONAL PADA MATERI PELUANG SISWA KELAS XII SMA - Santosa, Yoga Tegar; Antara, Setiya; Irmanopaliza, Ade; Ferdianto, Juli; Hidayati, Yulia Maftuhah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Correlational misconceptions experienced by students must be overcome so that they can better understand the relationship between concepts and avoid reasoning errors in solving problems. This study aims to explore the forms of correlational misconceptions experienced by students and analyze the types of limited interventions in each form of student correlational misconceptions on probability materials. This type of research is qualitative-case study. The research subjects were 10 grade XII students at SMA Negeri 1 Boyolali. Data collection uses participatory observation, document analysis, and in-depth interviews. The validity of the data uses triangulation methods. Data analysis includes reduction, presentation, and withdrawal of data conclusions. This study reveals four forms of correlational misconceptions grouped into three main categories. The first category has two misconceptions about students' inability to connect mathematical concepts or procedures logically. This misconception can be overcome by applying disequilibration strategies and cognitive conflicts in sequence. Meanwhile, the second and third categories each include one form of misconception. In the second category, there is a misconception about applying concepts or procedures that are irrelevant to a particular context. On the other hand, the third category is a misconception regarding the error of connecting specific events with general principles. Combination strategies involving disequilibration, cognitive conflict, and scaffolding effectively overcome misconceptions in the second and third categories. The results of these findings can be the basis for further research to develop a learning model that can anticipate the occurrence of correlational misconceptions in students.